Development of Guidelines and Continuing Professional Development (CPD) Program for Nursing - Mahmul Rivai Siregar; Tuti Afriani; La Ode Abd Rahman; Krisna Yetti; Dyah Fitri Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2026)
Professional development of nurses plays a crucial role in improving the quality of nursing services. The implementation of continuing competency development programs has not been optimal due to the absence of structured guidelines and programs at Hospital This lack of structure results in low consistency and uniformity in program implementation across nursing units. This study aims to develop a structured and sustainable professional development guideline and program for nurses that can serve as a reference for systematic and targeted implementation within the hospital environment. The study was conducted through a nursing management residency program held from May 27 to June 30, 2025. Data were collected through interviews, observations, and questionnaires distributed to nursing staff and nursing leadership. The questionnaire used the Q-PDN to measure various aspects of Continuing Professional Development (CPD) among nurses, with a Cronbach’s alpha reliability value of 0.89. Data analysis involved the Ishikawa diagram approach, SWOT analysis, and problem prioritization using the USG method. The analysis identified the absence of CPD guidelines and programs as the main problem, with the highest priority score. A draft guideline and CPD program were developed, covering staffing standards, facilities, implementation procedures, quality control, reporting, and follow-up mechanisms. Initial evaluation showed that 91% of stakeholders had a strong understanding of the document and provided positive feedback on its usefulness. The development of CPD guidelines and programs is a strategic step to strengthen the implementation of continuous professional development for nurses.